Severe anti-α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor encephalitis with prolonged hyperammonemia: a case report - Chunxia Yan; Lingling Bai; Jingwei Du; Zonglei Chong; Guangjun Xu; Xiaoqian Yang (BMC Neurology)
Abstract Background Anti-α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor encephalitis (Anti-AMPAR-E) is a very rare subtype of autoimmune encephalitis, typically presenting with memory decline, seizures, and changes in psychosis and behavior. Anti-AMPAR-E is often associated with the presence of neoplasms and generally has a poor prognosis. Currently, cases of severe anti-AMPAR-E, particularly those accompanied by hyperammonemia, are exceedingly rare. Case presentation A 66-year-old man was admitted to the hospital, complaining of deterioration in memory and confusion for at least 10 days and worsening for 3 days. The patient’s condition rapidly progressed to coma, which persisted for 2 months, manifesting as a fulminant course. At that time, his Glasgow Coma Scale (GCS) score was 6, and AMPAR antibodies were strongly positive in both serum and cerebrospinal fluid (CSF). Additionally, his serum ammonia levels consistently exceeded reference values during his hospital stay. Consequently, he was diagnosed with severe anti-AMPAR-E with prolonged hyperammonemia and treated with intravenous methylprednisolone pulse (IVMP) therapy, intravenous immunoglobulin (IVIG), and rituximab therapy until he regained consciousness. However, 10 months after discharge, he was readmitted to the hospital due to seizures and subsequently diagnosed with lung cancer. The patient eventually passed away at home. Conclusions Even if the short-term prognosis is good, regular tumor-related screening is essential for patients with severe anti-AMPAR-E to detect potential tumors early and improve long-term outcomes. Moreover, it is necessary to perform repeated ammonia level assessments and to adequately treat hyperammonemia.